1986
DOI: 10.2134/jeq1986.00472425001500020004x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Heavy Metals in Waste Drilling Fluids Under Conditions of Changing pH

Abstract: A laboratory study was conducted to determine the influence of pH on the distribution of arsenic (As), barium (Ba), chromium (Cr), and lead (Pb) in three different oil and gas well drilling fluid wastes. Samples were obtained from disposal pits and equilibrated in the laboratory under controlled conditions of pH. A sequential extraction procedure was then used to fractionate the selected elements into the fractions of aqueous, KNO3‐extractable, H2O‐extractable, NaOH‐extractable, EDTA‐extractable, and HNO3‐extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The fate of trace metals in soil following drilling‐fluid application has also been investigated. Some workers (Deeley and Canter, 1986) conducted fractionation studies that suggested trace metals would not be significantly released while others (Bates, 1988) found increases in plant available forms of trace metals and movement in a column study.…”
mentioning
confidence: 99%
“…The fate of trace metals in soil following drilling‐fluid application has also been investigated. Some workers (Deeley and Canter, 1986) conducted fractionation studies that suggested trace metals would not be significantly released while others (Bates, 1988) found increases in plant available forms of trace metals and movement in a column study.…”
mentioning
confidence: 99%
“…The problem of increased concentrations of some heavy metals caused by the application of crude oil-based fluids was pointed out by Nelson et al, 1984. When crude oil-based fluids were used as liming material, the expected positive changes in soil pH occurred (Deeley & Canter, 1986). As optimum soil reaction for the majority of cultivated plants is around the neutral pH value, liming is a desirable practice because under neutral to weakly alkaline conditions bioavailability of some heavy metals (except As, V, Mo, Co and Cr) decreases (Mathur et al, 1991;Dermatas & Meng, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Both organic and inorganic constituents were identified as potential contaminants. However, low pH values (<4.0) sufficient to result in significant release to trace elements from drilling fluids are unlikely due to their great neutralizing capacity (Deeley and Canter 1986). Plant uptake of Zn, Cu, Cd, Pb, and As was directly related to the concentrations of these trace elements added to soils by drilling fluids (Nelson et al 1984).…”
Section: Cals Normal Disposal Rates Of 10 Drilling Fluid Components mentioning
confidence: 99%